Report of the Minister of Foreign Affairs of the Czechoslovak Socialist Republic, Comrade Bohuslav Chnoupek, on the fundamental issues of the foreign policy of the country - Chnoupek, Bohus
En port.: Exposé of the Minister of Foreign Affairs B. Chnoupek, in the Federal Assembly of the Czechoslovak Socialist Republic on november 9, 1987